Optical coherence tomography angiography characterization of acute and late stage Purtscher retinopathy. Issue 4 (July 2018) - Gil, Pedro; Raimundo, Miguel; Marques, João P; Póvoa, João; Silva, Rufino
Purpose: To report a case of Purtscher retinopathy imaged with optical coherence tomography angiography. Methods: Case-report. Left eye fundoscopic examination in a 21-year old male after a road traffic accident with chest compression revealed multiple peri-papillary cotton-wool spots and intra- and pre-retinal hemorrhages. A diagnosis of Purtscher retinopathy was assumed. Results: In both the superficial and deep retinal plexuses, acute stage optical coherence tomography angiography identified multiple irregular areas of capillary non-perfusion that extended beyond the clinically visible peri-papillary cotton-wool spots. At 5-month follow-up, despite the clearing of visible cotton-wool spots, there were still permanent areas of irregular capillary non-perfusion and inner retina atrophy. These sequelae, along with a decrease in the peri-papillary retinal nerve fiber layer thickness, were consistent with a suboptimal visual outcome and a dense inferior arcuate scotoma. Conclusion: Baseline and follow-up optical coherence tomography angiography was able to detect, quantify, and map focal microvascular abnormalities at the level of the superficial and deep inner retinal vascular plexuses. These lesions were consistent with late stage structural and functional sequelae, conferring them prognostic value.